Caretas: festas e performance dos brincantes na cidade de Jardim-CE - Ulisses, Ivaneide Barbosa (2004)
The work has as object a party, in matter, the Party of the Grimaces, that happens annually (period of the Week Saint) in the municipal district of Garden, south of the State of Ceará. lhe research, is centered, in the manners as "Brincantes", "former - Brincantes" and organizers of the event live and they interpret the processes of accomplishment of the festivity. And how it is meant and resignificado in the daily of the city in the days of preparation and presentation of the Grimaces. lhe problem heads in the mat of studies in that the " parties " express conflicts, tensions, temporary dimensions of those social groups that execute them. The Party of the Grimaces, it is faced in the work while a staging " type, close to the codes of the popular theater. Sending to subjects as, production (producer); instruments (codes/supports); message (content/significance); reception (reading and reapropriação). In the case, the producing of the text, are the Grimaces and organizers of the festivity, theyare still those individuaIs that attend the presentation of " Brincantes ". lhe codes are formalized in the clothes of " Brincantes ", they are the masks, clothes, rattles, clubs, materiaIs of vegetable origin (straw, leaves...). Saint also the gestures, the said expressions, musicadas and the musical instruments. The support of the text is the bodies of the Grimaces. And as primordial element of the understanding of the message and reception of the text that it is the own articulation of group of the work the oral source it comes as primordial methodology.